2012
DOI: 10.1159/000335978
|View full text |Cite
|
Sign up to set email alerts
|

Low Diastolic Blood Pressure Is Associated with the Progression of Normal-Tension Glaucoma

Abstract: Aims: The objective of this study was to investigate the association between blood pressure (BP) and visual field defect progression in normal-tension glaucoma (NTG). Methods: The subjects were 35 consecutive patients with NTG who were admitted to Keio University Hospital for 24-hour intraocular pressure evaluation; all subjects underwent 6 or more visual field tests in either eye and were followed up for more than 5 years. Systolic and diastolic BPs were measured at 9.00 h. Subjects with negative regression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 57 publications
(44 reference statements)
0
21
0
1
Order By: Relevance
“…Evidence for the effect of blood pressure on glaucoma remains controversial. Although there are some studies that showed relationship between low DBP, high SBP and low MOPP with a high prevalence of open-angle glaucoma 54 and low DBP with the progression of NTG, 55 other epidemiological studies failed to found significant association with hypertension and glaucoma. 13 As our study subjects consisted of adults under 40 years old, we presume that the relationship between blood pressure or ocular perfusion pressure and open-angle glaucoma with normal baseline IOP is not clear in this age group.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence for the effect of blood pressure on glaucoma remains controversial. Although there are some studies that showed relationship between low DBP, high SBP and low MOPP with a high prevalence of open-angle glaucoma 54 and low DBP with the progression of NTG, 55 other epidemiological studies failed to found significant association with hypertension and glaucoma. 13 As our study subjects consisted of adults under 40 years old, we presume that the relationship between blood pressure or ocular perfusion pressure and open-angle glaucoma with normal baseline IOP is not clear in this age group.…”
Section: Discussionmentioning
confidence: 97%
“…It is worthwhile noting that all these population-based studies only looked at IOP and BP parameters during daytime, unlike our study that looked at these parameters over a 24-h period. Okumura et al found that low diastolic BP was associated with glaucomatous VF progression in subjects with NTG [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is a particularly well-established risk factor for glaucomatous optic neuropathy (GON). 45,46 As a consequence, blood pressure should not be lowered too rigorously in patients suffering from both systemic arterial hypertension and glaucoma. Spontaneous systemic hypotension [as it occurs particularly in the context of primary vascular dysregulation (PVD)] is very often observed in patients with normal tension glaucoma (NTG).…”
Section: Pathophysiology Of Tissue Damage: An Ophthalmologic Perspectivementioning
confidence: 99%